Implications of Talent Definitions for Talent Management Practice - Agnieszka SKUZA; Habte G. WOLDU; Shawn ALBORZ (Communications of International Proceedings, 2020)
In recent years, talent management has experienced increased attention from both scholars and practitioners. Globalization, technological developments, demographic changes, and the current pandemic influenced fierce competition for talents who will secure organizational development in a turbulent business environment. While organizations increasingly consider talent management central to the competitive advantage, only a small percentage of companies consider their talent management effective. One of the challenges is the lack of agreement both among academics and organizations on who the talent is. This paper contributes to the theoretical literature on talent management by presenting the implications of different talent definitions for talent management practice. Understanding these implications enables organizations to use talent management practices more effectively.
Keywords: Talent Management; Human Capital; Human Resource Management.